2017
DOI: 10.1038/s41598-017-10672-9
|View full text |Cite
|
Sign up to set email alerts
|

Nanocurcumin is superior to native curcumin in preventing degenerative changes in Experimental Cerebral Malaria

Abstract: Curcumin has many pharmacological activities despite its poor bioavailability and in vivo stability. Here, we show that a nanoformulated curcumin (PLGA-curcumin) has better therapeutic index than native curcumin in preventing the onset of neurological symptoms and delaying the death of mice in experimental cerebral malaria. Oral PLGA-curcumin was at least as effective as native curcumin at a 15-fold lower concentration in preventing the breakdown of blood-brain barrier and inhibition of brain mRNAs for inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(65 citation statements)
references
References 40 publications
3
62
0
Order By: Relevance
“…Our findings are consistent with a number of studies where encapsulation of curcumin in various nanoformulations has been shown to improve its effects on different cellular parameters in animal and cell based systems by enhancing stability and bioavailability. For example, oral feeding of PLGA encapsulated curcumin exhibited increased bioavailability through enhanced retention in the brain and prevented the breakdown of blood-brain barrier [9]. Importantly, the improved performance of nanocurcumin is suggested to be mediated by decreased inflammatory cytokines, chemokine receptor and increased anti-inflammatory cytokines [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings are consistent with a number of studies where encapsulation of curcumin in various nanoformulations has been shown to improve its effects on different cellular parameters in animal and cell based systems by enhancing stability and bioavailability. For example, oral feeding of PLGA encapsulated curcumin exhibited increased bioavailability through enhanced retention in the brain and prevented the breakdown of blood-brain barrier [9]. Importantly, the improved performance of nanocurcumin is suggested to be mediated by decreased inflammatory cytokines, chemokine receptor and increased anti-inflammatory cytokines [9].…”
Section: Discussionmentioning
confidence: 99%
“…For example, oral feeding of PLGA encapsulated curcumin exhibited increased bioavailability through enhanced retention in the brain and prevented the breakdown of blood-brain barrier [9]. Importantly, the improved performance of nanocurcumin is suggested to be mediated by decreased inflammatory cytokines, chemokine receptor and increased anti-inflammatory cytokines [9]. Similarly, enhanced antiangiogenic effects of curcumin including inhibition of HUVEC proliferation, migration, invasion, and tube formation were noticed in human liver cancer SMMC 7721 cells treated with curcumin encapsulated in pHsensitive polymeric nanoparticles [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The curcuminoid complex, found in the rhizome of turmeric (2.5-6%), contains CUR, demethoxycurcumin, and bis-demethoxycurcumin [11].…”
Section: Curcuminmentioning
confidence: 99%
“…Henceforth, Curcumin reach brain in biological effective concentration and ameliorate neurodegeneration (Begum et al, 2008;Schiborr et al, 2010). To further increase the bioavailability of Curcumin, researchers have been designed different nanoparticles (Nanocurcumin) to enhance its pharmacological activity (Barbara et al, 2017;Dende et al, 2017). In conclusion, our data provide evidence that Curcumin could be used for the therapeutics of CGG associated diseases FXTAS and FXPOI.…”
Section: Resultsmentioning
confidence: 65%